Craig R. Nethercott & David M. Eisenberg (eds): Islamic ﬁnance: law and practice - Oseni, Umar Aimhanosi (Springer Netherlands, 2012)
With the phenomenal growth in Sharī‘ah compliant products across the world, the application of Islamic law in commercial transactions has now transcended the natural borders of the Muslim world. Islamic finance has continued to grow in an amazing manner with the latest data on Sharī‘ah compliant assets put at $USD 1.3 trillion by the end of 2011. As a consequence of the tremendous growth witnessed in the Islamic finance industry within the past two decades, scholars have continued to provide the conceptual framework to guide current practices in the industry. Therefore, this book is one of the most detailed analyses of different aspects of Islamic finance from the legal and regulatory perspectives. More often than not, the legal dynamics of Islamic finance products have been a neglected field in Islamic finance. Though scholarship on Islamic finance has mushroomed within the past decade, there is a subtle neglect of this area of research, which in the final analysis has far-reaching implications on the future of the entire industry.